REVITALISASI MASJID BERBASIS PEMBERDAYAAN SOSIAL KEAGAMAAN DALAM UPAYA PENGUATAN AQIDAH DAN KARAKTER MASYARAKAT ISLAMI - Zulkarnaen, Iskandar; Bishri, Musthofa (Universitas Al-Amien Prenduan, 2024)
This community service activity focuses on revitalizing mosques as centers of empowerment in strengthening the religious beliefs of communities based on social and religious values. The main problem faced by communities is the decline in the function of mosques as centers for community development. Mosques are more often understood as places of ritual worship rather than spaces for social, educational, and spiritual empowerment. This situation has led to a weakening of faith understanding, low community participation in religious activities, and a decline in social solidarity based on Islamic values. The community service method is carried out through a participatory and collaborative approach involving mosque administrators, religious leaders, youth, and the surrounding community. The stages of the activity included: (1) analysis of the needs and potential of mosques as centers for da'wah and empowerment; (2) training in mosque management and capacity building for administrators; (3) aqidah guidance and thematic Islamic studies; (4) development of religious social programs such as Al-Qur'an literacy, mosque-based economics, and social community activities. The results of the community service show that the revitalization of mosques has been able to increase the strategic role of mosques as spiritual and social centers for the community. The community has begun to actively participate in religious and social activities initiated by mosques. Mosque administrators have also shown an increase in capacity in program management and congregation guidance. In addition, the community's awareness of faith has grown stronger, as evidenced by increased enthusiasm for ukhuwah (brotherhood), social awareness, and a more moderate understanding of religion. Thus, mosque revitalization has proven to be an effective means of sustainable social and religious community empowerment.